A comparison of the knowledge and attitudes of concussion within higher and lower leagues of the community rugby union game. (November 2022) - Oliver, Ben; Ashton, Jonty; Welsby, George; Simpson, Andrew
Abstract: Objectives: The Rugby Football Union (RFU) HEADCASE initiative aims to educate coaches, referees, and players on concussion. Concussion in community rugby is under-reported. Therefore, players can play a role in concussion safety if they have adequate knowledge and safe attitudes. The study aimed to evaluate and compare the concussion knowledge and attitudes and Return to Play (RTP) of the community rugby union game. Design: A descriptive, cross-sectional study. Participants: Participants (n = 87) were from level 4 or level 8 of the English rugby union league system. Main outcome measures: A modified Rosenbaum Concussion Knowledge and Attitudes Survey-Student Version (RoCKAS-ST) questionnaire was distributed to semi-professional and amateur clubs to evaluate players concussion knowledge index (CKI) and concussion attitudes and behaviours index (CAI) regarding RTP. Results: No statistically significant differences existed relating to knowledge, behaviours or attitude. Some worrying gaps in knowledge were identified. Conclusions: Findings show that community rugby union players are knowledgeable about concussion and have shown safe attitudes, however this doesn't always translate to safe behaviours. There are some gaps in their knowledge that must be addressed relating to coma and coherence of the athlete and in symptom recognition relating to sleep disturbances. Highlights: English community level Rugby Union players have good knowledge of the symptoms of concussion. There are some worrying gaps in players knowledge of concussion. English community level Rugby Union players generally display safe attitudes to concussion. Some unsafe attitudes were present and research is needed to investigate behavioural changes. Educational strategies should be modified to address gaps in knowledge. Abstract : There is rarely a risk to long-term health and well-being from multiple concussions.